Prevalence of Anxiety and Depression among Undergraduate Medical Students in Selective Medical Colleges of Bangladesh - Abbasy, Asma Akter; Johora, Fatema; Sakin, Saniad Ahmed; Khan, Abu Anis; Nilufar, Sonia; Ferdoush, Jannatul; Salam, Akif Ibn (IAHS Medical Journal, 2022)
Background: Mental well being of medical students has been a growing concern for several years. In Bangladesh, mental health problems are still considered as stigma. The aim of this study was to find out prevalence of anxiety and depression among medical students of Bangladesh. Materials and methods: This descriptive cross-sectional study was designed to find out the prevalence of anxiety and depression among undergraduate medical students (4th year) of 2 medical colleges (Brahmanbaria Medical College and Army Medical College Bogura) of Bangladesh during the month of March, 2020. Hospital Anxiety and Depression Scale (HADS) was used as data collection instrument. Total 85 students participated in the study. Results: Among the participants, 53 (62.3%) were female and 32 (37.7%) were male. 20% students were suffering from borderline anxiety and 52.94% were suffering from abnormal level of anxiety. On the other hand, 28.24% were suffering from borderline depression and 30.59% were suffering from abnormal level of depression. Mean value of anxiety was 9.84 ± 3.8 and 11.55 ± 4.34 among male and female respectively and the difference was not significant. There were no significant difference among male and female students in anxiety and depression (9.84 ±3.8 vs 11.55±4.34, p=0.07 and 8.31±3.96 vs 9.40± 4.55, p=0.25). Conclusion: Most of students of selected medical colleges of Bangladesh had been suffering from different level of anxiety and depression during the study period. There is a need to identify the contributory factors as well as undertaking of proper measures in reducing those factors which in long run will be helpful for improvement of academic performance and professionalism. IAHS Medical Journal Vol 5(1), June 2022; 8-11